Optimal Resource Allocation in a Representative Investor Economy - Gomes, Orlando (2017)
The Ramsey–Cass–Koopmans neoclassical growth setup and the AK endogenous growth framework are two prototypes of a class of growthmodelswhere, by assumption, investment resources are always perfectly allocated to production. As a corollary, these models offer a partial view of the growth process circumscribed to a limit case, namely the most favorable case in which all possible frictions on the allocation of investment resources are absent. This paper adds to the conventional growth setup an optimal mechanism of assignment of investment resources that contemplates the possibility of inefficient allocation. In the assumed economy there is a single representative investor and a large number of firms that compete for the available resources. The new setup highlights how agency costs may deviate the economy from the benchmark growth outcome, potentially generating less desirable long-run results. The appeal of the proposed framework resides also on the fact that new determinants of growth emerge and take a leading role, namely the investor's sentiment and the quality of the firms' investment proposals.